Alkyl-and arylsulfanyl-substituted unsaturated carbonyl compounds. (2nd January 2017) - Kondrashov, Evgeniy V.; Romanov, Alexey R.; Ushakov, Igor A.; Rulev, Alexander Yu.
ABSTRACT: A method for the synthesis of captodative sulfanyl enals, enones and enoates via nucleophilic vinylic substitution of corresponding halogen-bearing derivatives has been developed. The one-pot treatment of the haloenoates, haloenones or haloenals with thiols in the presence of organic base leads either to vicinal dithiosubstituted carbonyl-bearing compound or captodative systems with good to excellent yield. The major reaction direction strongly depends on the type of base used. GRAPHICAL ABSTRACT: